Sweden's Pandemic Experiment - Bergmann, Sigurd; Lindström, Martin (Taylor & Francis, 2023)
This book considers Sweden's pandemic management which differed so significantly from much of the rest of the world: it provoked intense and wide-reaching interest, curiosity and criticism. Trans-disciplinary Swedish authors from the humanities, life sciences, social sciences, and cultural studiesuse a variety of tools to mine deeper into some of the central elements and dimensions in their country's pandemic management such as understandings of freedom, the execution of power, denialism, exceptionalism, patriotism, the role of expertise and trust in the national state to give a deeper understanding of Sweden's decisions, failures, successes, and the lessons to be learned. Aimed at readers with interest in global health and politics it will also be of interest in disciplines such as virology,epidemiology, history, cultural studies, ethics, media studies, medicine and economics. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.